Vital Pulp Therapy Using Resin-Modified Calcium Silicate for Permanent Teeth with Reversible Pulpitis: A Systematic Review - Vikri Sandya Dhika; Veriantara Satya Dhika (Medicinus, 2026)
Background: Resin-modified calcium silicate (RMCS) cements combine the bioactivity of traditional calcium silicates with the superior handling properties of resins. This systematic review and meta-analysis evaluate the clinical and radiographic success of RMCS compared to established capping materials in permanent teeth diagnosed with reversible pulpitis. Methods: Following PRISMA 2020 guidelines, comprehensive searches were conducted across PubMed, EMBASE, Scopus, and Web of Science from inception through April 11, 2026. We included randomized controlled trials assessing vital pulp therapy (indirect and direct pulp capping) using RMCS against active comparators (calcium hydroxide, Biodentine) with at least six months of follow-up. Risk ratios were pooled utilizing the inverse variance method with a DerSimonian-Laird random-effects model. Result: Six randomized controlled trials met the criteria for quantitative synthesis. Pooled data indicated that RMCS materials demonstrated robust overall clinical and radiographic success rates across diverse vital pulp therapy procedures at 12- to 36-month follow-ups. Subgroup analyses revealed that while RMCS performed equivalently to calcium hydroxide in indirect pulp capping, it exhibited slightly varied success rates when compared to pure calcium silicate cements like Biodentine during direct pulp capping, though statistical heterogeneity was observed across these subsets. Conclusions: RMCS serves as a highly effective and clinically pragmatic biomaterial for vital pulp therapy in teeth with reversible pulpitis. While providing excellent outcomes for indirect treatments, clinicians should weigh subtle performance differences against pure calcium silicates when managing direct pulp exposures.